ANALYSIS OF SERVICE USER SATISFACTION LEVEL OF SERVICE EFFECTIVENESS AND EFFICIENCY LEGAL STATUS AND CERTIFICATION OF SAMARINDA CLASS II KSOP SHIP - Fitria, Fitria; Purba, Damoyanto; Limakrisna, Nandan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze the legal status of the Samarinda Port Authority (KSOP) Class II Samarinda Office and service users' satisfaction with the effectiveness and efficiency of the Vessel Certification Department's services. In this study, data were collected through questionnaires distributed to service users who used the KSOP Samarinda Legal Status and Vessel Certification Division services. Respondents were asked to rate each variable using a Likert scale. Collected data were analyzed using descriptive statistical techniques and factor analysis. The survey results indicate that service users are generally delighted with the effectiveness and efficiency of the KSOP Class II vessel Samarinda's legal status and certification services. Based on the survey results, service users are generally satisfied with the legal status of KSOP Class II Samarinda and the effectiveness and efficiency of the Vessel Certification Department's services. However, efforts should be made to continuously improve service quality, especially regarding system reliability. The results of this study will help KSOP Samarinda identify areas for improvement to meet the needs and expectations of service users, thereby improving the satisfaction of future service users